Chitosan nanoparticles loaded with clove essential oil: Characterization, antioxidant and antibacterial activities - Hadidi, Milad; Pouramin, Shiva; Adinepour, Fateme; Haghani, Shaghayegh; Jafari, Seid Mahdi (Carbohydrate polymers, 2020)
[Display omitted] •Clove essential oil (CEO) was encapsulated into chitosan nanoparticles.•FTIR, X-ray diffraction and DSC confirmed the successful loading of CEO.•Sizes of CEO-loaded nanoparticles ranged from 223 to 444 nm.•Encapsulation improved the antioxidant and antibacterial activity of CEO. One of the recent trends in the food industry is application of natural antioxidant/antimicrobial agents. In this study, essential oil of clove buds was extracted and encapsulated in chitosan nanoparticles using a two-step technique of emulsion-ionic gelation. A good retention rate (55.8–73.4 %) of clove essential oil (CEO) loaded in chitosan nanoparticles was confirmed. Also, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and differential scanning calorimetry (DSC) analyses revealed the success of CEO encapsulation. Scanning electron microscopy (SEM) images illustrated regular distribution and spherical shape of nanoparticles with a size range of 223−444 nm. The antioxidant activity of CEO-loaded chitosan nanoparticles was higher than free CEO. Similarly, CEO-loaded chitosan nanoparticles had a high antibacterial activity against L. monocytogenes and S. aureus (inhibition halo diameter of 4.80–4.78 cm). This technique could improve the efficiency of CEO in food products and a delivery system for novel applications such as active packaging.